Practice level factors associated with enhanced engagement with practice facilitators; findings from the heart health now study - Jacqueline R. Halladay; Bryan J. Weiner; Jung In Kim; Darren A. DeWalt; Stephanie Pierson; Jason Fine; Ann Lefebvre; Monique Mackey; Dawn Bergmire; Crystal Cené; Kamal Henderson; Samuel Cykert (BMC, 2020)
Abstract Background Practice facilitation is a promising strategy to enhance care processes and outcomes in primary care settings. It requires that practices and their facilitators engage as teams to drive improvement. In this analysis, we explored the practice and facilitator factors associated with greater team engagement at the mid-point of a 12-month practice facilitation intervention focused on implementing cardiovascular prevention activities in practice. Understanding factors associated with greater engagement with facilitators in practice-based quality improvement can assist practice facilitation programs with planning and resource allocation. Methods One hundred thirty-six ambulatory care small to medium sized primary care practices that participated in the EvidenceNow initiative's NC Cooperative, named Heart Health Now (HHN), fit the eligibility criteria for this analysis. We explored the practice and facilitator factors associated with greater team engagement at the mid-point of a 12-month intervention using a retrospective cohort design that included baseline survey data, monthly practice activity implementation data and information about facilitator's experience. Generalized linear mixed-effects models (GLMMs) identified variables associated with greater odds of team engagement using an ordinal scale for level of team engagement. Results Among our practice cohort, over half were clinician-owned and 27% were Federally Qualified Health Centers. The mean number of clinicians was 4.9 (SD 4.2) and approximately 40% of practices were in Medically Underserved Areas (MUA). GLMMs identified a best fit model. The Model presented as odd ratios and 95% confidence intervals suggests greater odds ratios of higher team engagement with greater practice QI leadership 17.31 (5.24-57.19), [0.00], and practice location in a MUA 7.25 (1.8-29.20), [0.005]. No facilitator characteristics were independently associated with greater engagement. Conclusions Our analysis provides information for practice facilitation stakeholders to consider when considering which practices may be more amendable to embracing facilitation services.